Mengoptimalkan Perkembangan Fisik Motorik Anak dengan Metode Outdoor Learning melalui Miniatur Kegiatan Outbound - Astuti, Retno Dwi (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2018)
The aim of this research is to know how much Outdoor Learning method through outbond acticity miniature influence to optimalize the early chilhood?s physical motoric. The method uses quasi experimental with nonequivalent control group design. It conducted in Sekaran District, Lamongan Regency with total sample as many as 85 children from Muslimat NU Nurul Huda Kindergarten Sekaran, Muslimat NU Rahayu Miru Kindergarten, and Musimat NU Bunga Harapan Kindergarten Latek. The sample is divided into two group, that are control group and experimental group. The data acquired from observation and documentary. The result shows 1) outdoor learning through outbond activity miniature significantly influences through chilhood?s physical motoric, this proven from ANOVA test result which shows Fcount score as 247.182 bigger than Ftable as 3.11.  Based on data analysis, it can be concluded tha early childhood?s physical motoric can be optimalized with Outdoor Learning method through Outdoor miniature.